The Influence of Spirituality on the Resilience of Victims of Online Gender-Based Violence in Early Adulthood: Self-Esteem Mediation - Dyah Ayu Chandra Pertiwi; Berliana Widi Scarvanovi (Universitas Muhammadiyah Surakarta, 2025)
Easy internet access and rising usage intensity have contributed to the rise in Online Gender Based Violence (OGBV), with early adult showing the highest internet use and OGBV cases. Resilience has an important role for victims to deal with the negative impact. Spirituality is one predictor of resilience, but previous findings show a weak relationship between the two, so a mediator variable is needed. Spirituality, which also affects self-esteem, may help enhance resilience. This study aims to determine the role of self-esteem in mediating the effect of spirituality on resilience in early adult victims of OGBV. A total of 116 OGBV victims aged 18–25 and living in West Java participated by completing the CD-RISC, SWBQ and SLCS-R scale questionnaires online. Data were analyzed using path regression and bootstrapping with Process Macro for SPSS 4.2. The results showed that there was a significant effect of spirituality on resilience in early adult victims of OGBV by 0.0135 (p < 0.05). Then there is a significant effect of self-esteem on resilience in early adult victims of OGBV by 0.0000 (p < 0.05). Then it is proven that there is a role of self-esteem in mediating the effect of spirituality on the resilience of early adult victims of OGBV by 0.8463 (p < 0.05). Therefore, all hypotheses in this study are accepted. Spirituality contributes 56.82% to resilience through self-esteem, and the remaining 43.18% is explained by other variables excluded from the study. Practically, spiritual activities help boost self-esteem and resilience in OGBV survivors.